Patients' Choice, Consent, and Ethics in Patient Blood Management. (17th August 2022) - Isbister, James P.; Pearse, Bronwyn L.; Delaforce, Alana S.; Farmer, Shannon L.
Abstract : The goal of patient blood management (PBM) is to optimize clinical outcomes for individual patients by managing their blood as a precious and unique resource to be safeguarded and managed judiciously. A corollary to successful PBM is the minimization or avoidance of blood transfusion and stewardship of donated blood. The first is achieved by a multidisciplinary approach with personalized management plans shared and decided on with the patient or their substitute. It follows that the physician-patient relationship is an integral component of medical practice and the fundamental link between patient and doctor based on trust and honest communication. Central to PBM is accurate and timely diagnosis based on sound physiology and pathophysiology as the bedrock on which scientifically based medicine is founded. PBM in all disease contexts starts with the questions, "What is the status of the patient's blood?" "If there are specific abnormalities in the blood, how should they be managed?" and "If allogeneic blood transfusion is considered, is there no reasonable alternative therapy?" There are compelling scientific reasons to implement a nontransfusion default position when there is clinical uncertainty and questionable evidence of clinical efficacy for allogeneic blood transfusion due to known potential hazards. Patients must be informed of their diagnosis, the nature, severity and prognosis of the disease, and treatment options along with risks and benefits. They should be involved in decision-making regarding their management. However, as part of this process, there are multifaceted medical, legal, ethical, and economic issues, encompassing shared decision-making, patient choice, and informed consent. Furthermore, variability in patient circumstances and preferences, the complexity of medical science, and the workings of health care systems in which consent takes place can be bewildering, not only for the patient but also for clinicians obtaining consent. Adding "patient" to the concept of blood management differentiates it from "donor" blood management to avoid confusion and the perception that PBM is a specific medical intervention. Personalized PBM is tailoring the PBM to the specific characteristics of each patient. With this approach, there should be no difficulty addressing the informed consent and ethical aspects of PBM. Patients can usually be reassured that there is nothing out of order with their blood, in which case the focus of PBM is to keep it that way. In some circumstances, a hematologist may be involved as a patient's blood advocate when abnormalities require expert involvement while the primary disease is being managed. Abstract :